2023
DOI: 10.1128/msystems.01211-22
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Dynamics of Coastal Viral Community Structure and Potential Biogeochemical Roles Affected by an Ulva prolifera Green Tide

Abstract: To the best of our knowledge, this study is the first to investigate the responses of viruses to the world’s largest macroalgal green tide. It revealed the spatiotemporal dynamics of the unique viral assemblages and auxiliary metabolic genes (AMGs) following the variation and degradation of Ulva prolifera . These findings demonstrate a tight coupling between viral assemblages, and prokaryotic and eukaryotic abundances were influenced by the green tide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 82 publications
0
5
0
Order By: Relevance
“…These results indicated the dynamic relationship between viruses and their hosts in coastal ecosystems. The abundance of phage vB_TgeS_JQ at the outbreak of U. prolifera may be due to the accumulation of a large number of algae-derived polysaccharides after the arrival of algal blooms ( 47 ). Flavobacteriia are the dominant prokaryotic group during this green tide period ( 17 , 65 ), as they can degrade algae-derived polysaccharides ( 66 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results indicated the dynamic relationship between viruses and their hosts in coastal ecosystems. The abundance of phage vB_TgeS_JQ at the outbreak of U. prolifera may be due to the accumulation of a large number of algae-derived polysaccharides after the arrival of algal blooms ( 47 ). Flavobacteriia are the dominant prokaryotic group during this green tide period ( 17 , 65 ), as they can degrade algae-derived polysaccharides ( 66 ).…”
Section: Resultsmentioning
confidence: 99%
“…The relative abundances of vB_TgeS_JQ were calculated using CoverM v0.6.1 ( https://github.com/wwood/CoverM ) and expressed by RPKM (reads per kilobase per million mapped reads) (v0.3.1) with parameters: -m rpkm--min-read-percent-identity 0.95--min-read-aligned-percent 0.75 ( 45 , 46 ). The quality-controlled reads of 154 Global Ocean Viromes (GOV 2.0) and Qingdao coastal virome (QDCV) data sets ( 47 ) were mapped to the vB_TgeS_JQ genome using metagenomics tool minimap2. QDCV data set was selected because the phage was isolated during an outbreak of U. prolifera in coastal Qingdao, during which Flavobacteriia was the dominant strain.…”
Section: Methodsmentioning
confidence: 99%
“…These results demonstrate the dynamic relationship between prokaryotic and eukaryotic components of the coastal ecological system. The abundance of this phage significantly increased might be with the accumulation of high amounts of algal-derived DOM after the bloom arrival (Han et al, 2023). By the end of the bloom termination stage, most of the labile DOM had been utilized by bacteria, it might result the decrease of viral abundance like phage vB_PhoS_XC.…”
Section: Abundance and Ecological Function Of Phage Vb_phos_xcmentioning
confidence: 98%
“…Every year from June to July, a large-scale U. prolifera bloom typically occurs in Qingdao. This bloom rapidly causes a decline in inorganic carbon, increasing the pH of the seawater (Han et al, 2023). When the bloom terminates, pH, DOM, DOC, and nutrients are significantly altered to an extent that disrupts the dynamic balance of bacterial community structure and function (Li H et al, 2016;Zhang and Wang, 2017;Chen et al, 2020;Liang et al, 2021).…”
Section: Abundance and Ecological Function Of Phage Vb_phos_xcmentioning
confidence: 99%
“…The higher contribution of the mec gene at 1,000 m seems to assist nutrient acquisition in this deep ecosystem, since the gene encodes for a sulfur carrier protein that aids the biosynthesis of cysteine (Hesketh-Best et al, 2022) and possibly the degradation of sulfated organic matter (Han et al, 2023), thus viral particle formation too. Despite the low understanding of the role of mec in the viral genomes, it seems that recent investigations on viral implications on the oceanic sulfur cycling are reinforced and extended by our findings (Kieft et al, 2021); viral genes related to sulfur relay were found at 1,000 m, thus possibly contributing to sulfur's budget manipulation.…”
Section: Same Lysis Rate At All Depths-different Taxa and Amgs Involvedmentioning
confidence: 99%